2012
DOI: 10.1021/jp2091363
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions between Doxorubicin and β-Cyclodextrin 4-Methoxyphenol Conjugates

Abstract: Newly synthesized derivatives of β-cyclodextrin, mono(6-deoxy-6-(1-1,2,3-triazo-4-yl)-1-propane-3-O-(4-methoxyphenyl))β-cyclodextrin (1) and mono(6-deoxy-6thio(1-propane-3-O-(4-methoxyphenyl))) β-cyclodextrin (2) were designed to be receptors of the anticancer drug doxorubicin, which could potentially decrease the adverse effects of the drug during treatment. In both aqueous and aqueous dimethyl sulfoxide (DMSO) solutions, doxorubicin forms an inclusion complex with the new cyclodextrin derivatives with format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 27 publications
(39 reference statements)
1
42
0
1
Order By: Relevance
“…Mono(6‐deoxy‐6‐(1‐1,2,3‐triazo‐4‐yl)‐1‐propane‐3‐ O ‐(phenyl)) β ‐CD was synthesized according to the procedure described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mono(6‐deoxy‐6‐(1‐1,2,3‐triazo‐4‐yl)‐1‐propane‐3‐ O ‐(phenyl)) β ‐CD was synthesized according to the procedure described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The aim of this work is to present that compressed sensing 2D NMR spectra allow for the full spectral assignment of near‐symmetric mono(6‐deoxy‐6‐(1‐1,2,3‐triazo‐4‐yl)‐1‐propane‐3‐ O ‐(phenyl)) β ‐CD. In this functionalized CD, designed to be a receptor of the anticancer drug doxorubicin, one sugar unit was modified at the C6 position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculation of Binding Constant K of 3b to DOX: It has been well reported in the literature that, addition of native γ-CD added to DOX at a ratio of up to 5000 : 1 could significantly stabilize DOX in aqueous solution via complex formation. 32) Other reports, 33) in which DOX encapsulation within CDs could significantly lower the fluorescence and absorbance signals of the guest molecule, demonstrated that CDs can be considered as a fluorophore quencher for DOX. Therefore, the binding constant can be calculated according to modified Stern-Volmer 24) Eq.…”
Section: )mentioning
confidence: 99%
“…[34] CyD chemical modification, by covalently attaching the appropriate moieties, can substantially increase the stability of the CyD-drug complex and such measures have been taken as a means for making complex-controlled target drug carriers. [34][35][36][37][38] Additionally, the appended group contains cyanine dyes, with long wavelength colorimetric and fluorometric photoactivities, as cyanine-CyD carriers can also be useful for optical and near-infrared fluorescence imaging in living cells or biological tissues.…”
Section: Introductionmentioning
confidence: 99%